Anatomic study of portal vein: transpancreatic vessels injuries approach - Mantovani,Mario (2002)
Introduction: The commitment of the great blood-vessels make up a situation of great complexity and a high rate of the complications and mortality patients with abdominal trauma. The injury of the portal vein matters because of the difficulty on the diagnosis and the approach surgery. Objective: To set the standard on the transverse section of the pancreas looking for a safer surgical access to repair the portal vein injuries. Methods: A quantitative analysis was performed to characterize the anatomical relationship between the portal vein and their tributaries relating them to the pancreas. On these corpses, the measurements of a anatomical triangle were studied. It base was the upper limit of the superior mesenteric vein and the initial portion of the portal vein; the apex, a point located on the upper limit of the confluence of the splenic vein and superior mesenteric vein, situated at the middle line of the superior mesenteric_ vein. Results: The portal vein is formed 3.24cm from the internal border of the duodenal arc at a distance of 1.61cm and 1.07 from the inferior and superior pancreas borders, respectively. Conclusion: The present study allow us to conclude that, to have access to the origin of the portal vein, in case of trauma of this vessel, one should proceed a transverse section of the neck of the pancreas next to the superior mesenteric vein, because its confluence with splenic vein occur, on average, 1.07cm and 1.61cm from the superior and inferior border of the gland, respectively.